2002
DOI: 10.1067/mjd.2002.125075
|View full text |Cite
|
Sign up to set email alerts
|

Medium-dose 308-nm excimer laser for the treatment of psoriasis

Abstract: A thrice-weekly, medium-dose irradiation schedule with the 308-nm laser can effectively clear localized plaque-type psoriasis in fewer treatments with an overall lower cumulative dose, compared with standard phototherapy. This innovative UV device allows specific targeting of affected sites without needless exposure of unaffected skin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
66
1
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 16 publications
0
66
1
3
Order By: Relevance
“…Two independent studies reported that during treatment with the 308 nm excimer UVB laser, approximately 40% of patients developed blisters, some needing 7-14 days until complete healing. 14,20 In the current study, we have demonstrated that the use of LED technology results in similar clinical outcome as that of the 308 nm laser, 21 and has a better side-effect profile. Eight weeks of targeted phototherapy using UVB-LEDs resulted in similar decreases in PSI scores and improvement rates as targeted delivery with the BClear system (a UVB lamp which has the peak emission of 305-313 nm).…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Two independent studies reported that during treatment with the 308 nm excimer UVB laser, approximately 40% of patients developed blisters, some needing 7-14 days until complete healing. 14,20 In the current study, we have demonstrated that the use of LED technology results in similar clinical outcome as that of the 308 nm laser, 21 and has a better side-effect profile. Eight weeks of targeted phototherapy using UVB-LEDs resulted in similar decreases in PSI scores and improvement rates as targeted delivery with the BClear system (a UVB lamp which has the peak emission of 305-313 nm).…”
Section: Discussionmentioning
confidence: 70%
“…Mineral oil has been frequently used in targeted phototherapy as it does not absorb radiation, and by decreasing the reflectance it increases the therapeutic effect of UV radiation. 21,25 The disadvantage of both the 308 nm laser and the BClear system is that they are limited to outpatient use. A fundamental requirement of successful phototherapy is application of several treatments over a short time period, resulting in frequent clinic visits which leads to low compliance.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Für diese Modalität wurden Studien mit Behandlungsfrequenzen von zwei [181], drei [182][183][184][185][186], fünf [187,188] [191], zweimal [192][193][194], dreimal [147,184,195,196] oder 4 x/Wo [193,197] In mehreren kleinen [195,[199][200][201] sowie einer größeren nichtrandomisierten Studie [202] [197,212] treten jedoch mit ca. 5 % eher selten auf [197].…”
Section: Uv-b (Breitspektrum)unclassified
“…The second, which includes agent-based models that involve keratinocytes under certain biological and physical rules. Both models simulate the multi-layers of the skin regulated by cell differentiation, proliferation, migration, and death in which certain biochemical factors change the behaviors of the epidermal structure [25]. There has been research performed by mathematicians jointly with biologists to investigate the psoriasis pathogenesis dynamics and treatments effects.…”
Section: Introductionmentioning
confidence: 99%